Synthesis and Evaluation of Mannich Base Derivatives of Hexyl Ferulate as Antibacterial and Antioxidant Agents - Kadek Devi Arum Savitri; Hayun Hayun; Herman Suryadi (Green Publisher Indonesia, 2026)
Antimicrobial resistance (AMR) constitutes a serious global health issue, with its impact being especially pronounced in developing countries like Indonesia. Developing new antibacterial and antioxidant agents through structural modification offers a promising strategy to address AMR. Ferulic acid, a natural phenolic compound with known biological activity, has limited bioavailability. To enhance its potency, structural modification into hexyl ester and Mannich base derivatives was performed. Ferulic acid (1) was synthesized via solvent-free Knoevenagel condensation, converted to hexyl ferulate (2) through esterification with hexyl bromide, and further modified with dimethylamine (3a), diethylamine (3b), morpholine (3c), and 2,6-dimethylmorpholine (3d). The antioxidant assays (DPPH and FRAP) showed that 3a–d had IC₅₀ values of 1.89–22.67 µM and EC₅₀ values of 0.34–4.08 µM. Compounds 3b (EC₅₀ 0.34±0.00 µM) and 3d (IC₅₀ 1.89±0.00 µM) exhibited strongest antioxidant activity, exceeding the activity of ascorbic acid. Antibacterial testing showed 3d produced the largest inhibition zones, up to 26.90 mm at 3 mg/mL against S. aureus. MBC testing confirmed that 3b was the most active (0.75–3.00 mg/mL). The enhanced activities correlated with increased lipophilicity (logP 3.32–4.25). Overall, Mannich base substitution of hexyl ferulate significantly improved antioxidant and antibacterial properties, suggesting its potential as a lead scaffold for developing agents against resistant pathogens.